Reduced graphene oxide-ZnO hollow microsphere composite for supercapacitor applications - Abdullah, Abqari Luthfi Albert; Radiman, Shahidan; Chiu, Wee Siong; Abdul Hamid, Muhammad Azmi; Badrudin, Fadhlul Wafi (Universitas Mercu Buana, 2025)
Through a facile solvothermal synthesis process, a reduced graphene oxide-ZnO microsphere composite was produced at 180 °C for 24 hours. Raman spectroscopy, X-ray diffraction, field emission scanning electron microscopy, and transmission electron microscopy were used to analyze the morphological structures of the material. The analysis revealed that hexagonal phase wurtzite ZnO nanoparticles assembled homogeneous microspheres, decorated on the graphene sheets by graphene oxide functional groups. The ZnO nanoparticles are about 30 nm in size and the microspheres are hollow. A possible growth mechanism for the formation of ZnO hollow microspheres anchored on graphene sheets has been proposed. Cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance were used to evaluate the electrochemical performance of the composite. At a scan rate of 1 mV/s, the reduced graphene oxide-ZnO hollow microsphere composite electrode demonstrated an enhanced specific capacitance of 40.70 F/g with energy and power densities of 5.75 Wh/kg and 1.97 kW/kg, respectively.